A Scoping Review of Factors Associated with Self-Management Among Patients with Breast Cancer - Ruth Jamlaay; Restuning Widiasih; Mira Trisyani (Universitas STRADA Indonesia, 2025)
Self-management in patients with breast cancer plays an essential role in improving the quality of life of breast cancer patients. Self-management behaviour changes along with the treatment period and varies in patients with different demographic and psychosocial characteristics. However, systematic identification of self-management factors in this population is still lacking. This review aimed to identify factors that influence self-management in patients with breast cancer. This study used a scoping review. Literature was searched from three databases: EbscoHost: Medline Ultimate, Pubmed, and Scopus, and additional literature was identified using Google Scholar, using the keywords